Psychological aspects met in the start-up stage of entrepreneurial activity - DRAGOMIR, Robert Gabriel (Annals of Spiru Haret University. Economic Series, 2012)
The present paper proposes to focus on the important psychological characteristics implied in the activity of start-up a business. At the beginning, we present the definition and the specific points of an entrepreneur and also of an entrepreneurial activity. Then we restrict the sphere to the psychological aspects connected to the start-up business activity: the courage, the self trust, the independence attitude, the intuition, the professional training and the environment knowledge, the ability of adapting, the great availability for work, the perseverance, good organiser, a good communicator, respect for the collaborators, positive thinking, socially active. In the end, we jump at the conclusions and talked about the importance and the roles of the projects financed by the European Union, the Romanian Government, the Social European Fund and Structural Instruments.